'Study in Estonia': the strategic implications of hosting international students on Estonia's tourism economy. Issue 2 (2nd April 2020) - Jarvis, Jeff
ABSTRACT: In the context of increasing global mobility, international university students have previously been identified as a high yield and beneficial visitation market. A quantitative study of 289 short-term international university students in Estonia confirmed that they are high-yield, long-staying, low-leakage, counter-seasonal visitors who stimulated significant visiting friends and relatives tourism. The economic benefits derived from these students spread throughout Estonia and the wider Baltic tourism economy. Strategically, they demonstrated a strong capacity to generate positive word of mouth and become brand ambassadors, assisting in the rebranding of 'post-Soviet' tourism economies with limited marketing resources such as Estonia.